Biology as Destiny in Gender Inequality - Sharma, Sharada Devi (Research Nepal Journal of Development Studies, 2021)
Generally differentiating men and women in society as a gender study is itself increasing the discrimination. It is in the name of eliminating discrimination activists are uniting, registering, advocating the weaker section of the society for political benefit. The weaker section is being stronger to fight against the stronger section to intensify the conflict for political benefit. The recent accident of Rukum district is the product of conflict-led politics of modernity. A Dalit boy went to marry his non-Dalit love with some of his friends but her people made them jump on the Karnali River to save their lives but killed. The incident was highly politically motivated. Until we follow the philosophy of modernity, the same kind of incidents may repeat time and again. The study is to analyze biology as destiny in gender inequality. Methodologically the study is a critical analysis of modernism on the issues of gender inequality. Men are men and women are women with pride, no regression at all. No one can eliminate destiny or Prarabdha but we can neutralize it.